Russian society in the context of crisis realities: internal and external factors - Gorshkov, Mikhail K. (Journal of the Belarusian State University. Sociology, 2019)
The paper focuses on the results and main conclusions of a multidimensional analysis of the state and dynamics of Russian society in a new reality, mediated by external and internal threats and risks aggravated by the consequences of the economic crisis that started in Russia in 2014. The empirical basis for it is formed by the results of the national sociological monitoring survey, covering the period from 2014 to present, which is carried out by the Institute of Sociology of the Russian Academy of Sciences research team (since July 2017 – the Federal Center of Theoretical and Applied Sociology of the Russian Academy of Sciences. System-wide and contextual conclusions obtained through the survey allow to apply to sociological diagnostics of the life choices and vital priorities of modern Russians. Particular attention is given by the author to the adaptive capacities of Russian population, adaptation plans and strategies used within different social groups, in-depth analysis of Russians’ economic and political behaviour in crisis. The paper also considers the impact of crisis on material and economic aspects of Russian everyday life, and Russians’ satisfaction with the different issues of their existence. A systematic change in employer-employee relationship is diagnosed. The socio-psychological dynamics of Russian society is assessed during the period under review. The author explores sustainability and volatility of Russians’ worldviews, values and aspirations, as well as the resources for social integration in a poly-ethnic and religious space of Russia.
Keywords: Russian society; mass consciousness; crisis situation; economic and political patterns of behaviour; adaptation; vital priorities and life choices; social resource; integration; consolidation; system of norms and values